Klasifikasi Kelayakan Susu Sapi UHT berdasarkan PH, Warna, dan Aroma menggunakan Metode Naive Bayes berbasis Arduino - Muhammad Daffa Bintang Nugroho; Dahnial Syauqy; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Ultra High Temperature cow's milk is a type of milk that is widely consumed by humans from children to adults because milk has a myriad of health benefits, but if the cleanliness of the processing is not maintained, milk quickly becomes unfit for consumption and can cause various adverse effects for a person who consume it. There are many ways to determine the appropriateness of consuming milk, such as by looking at its color, smelling the aroma, or tasting the milk, but these methods are ineffective and raise doubts about whether milk is still suitable or not suitable for consumption. This study designed a system to determine the feasibility of Ultra High Temperature cow's milk based on pH parameters, ammonia gas content, and color. To determine the value of each parameter, a PH 4502C sensor, MQ135 gas sensor, and TCS3200 color sensor are used to carry out the process of determining the feasibility of milk using the Naive Bayes classification method which is processed with the Arduino Mega 2560 microcontroller. The results of the accuracy of the system test to determine the feasibility of milk Ultra High Temperature cattle based on pH parameters, ammonia gas content, and color with the Naive Bayes classification method using 40 training data and 20 test data is 85% with a computation time of 1,911 seconds.